Constructivism and creative activity as factors of modern education development - E. V. Savelova (Высшее образование в России)
The article analyzes the processes in modern culture and in education. The author accentuates the mission of education in the process of acculturation, shows such values of modern education as constructivism and creative activity, which can form the Man of Culture. Special attention is paid to the position of educational institutions with a creative bias, such as institutes of Arts and Culture, which provide training of specialists with a great creative potential. The author strongly argues that most of the formalized criteria used for the educational institutions assessment are not applicable for such special institutes. The quality of educational process there should be evaluated according to special criteria taking into consideration the specificity of educational programs.